2019
DOI: 10.15544/mts.2019.34
|View full text |Cite
|
Sign up to set email alerts
|

Audit in the State Economic Security System

Abstract: In the research it is proved that constant and progressive development of any country is impossible without providing economic and social security processes. The aim of the article is to determine the state and development trends of state and independent professional audit as a key imperative for the formation of economic security. It is justified that due to financial globalization, complexity and versatility of both interstate and domestic correlation, economy development dynamics are sensitive to crisis occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 7 publications
0
7
0
3
Order By: Relevance
“…For example, countries such as Switzerland and Norway have seen results over time in improving the relative efficiency of tax systems, along with a growing convergence in tax simplification trends (Nguyen T. et al, 2021) The transition to a constitutional mode of government was everywhere accompanied by the building of a democratic state based on new values (Afonso, 2006, Alshrouf, 2019Blesse et al, 2019). In this sense, the role of the highest bodies of state control has always been to ensure that these values are respected and to foster greater citizen participation in governance (Koval et al, 2019;Belmonte-Martin et al, 2021, Polzer, 2021. Good governance of the state assumes that the constitutional rights of citizens are exercised for the benefit of the new democracy (Goyette, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, countries such as Switzerland and Norway have seen results over time in improving the relative efficiency of tax systems, along with a growing convergence in tax simplification trends (Nguyen T. et al, 2021) The transition to a constitutional mode of government was everywhere accompanied by the building of a democratic state based on new values (Afonso, 2006, Alshrouf, 2019Blesse et al, 2019). In this sense, the role of the highest bodies of state control has always been to ensure that these values are respected and to foster greater citizen participation in governance (Koval et al, 2019;Belmonte-Martin et al, 2021, Polzer, 2021. Good governance of the state assumes that the constitutional rights of citizens are exercised for the benefit of the new democracy (Goyette, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nor et al (2019) evidenced a positive impact of audit opinion on the publication of Indonesian financial statements on websites. Koval, Nazarova, Hordopolov, Kopotiienko, Miniailo, & Diachenko (2019) discuss the role of public audits in the investor's confidence in the economic security of the State relating to disclosure of audit opinion on supporting public institutions.…”
Section: Disclosure and Auditmentioning
confidence: 99%
“…Analysis of scientific publications has shown that much of the current research on public sector auditing is mainly explorative (Nazarova et al, 2019; Sembiyeva et al, 2020; Sultanova et al, 2020) or comparative (Dimitrova et al, 2019) in nature, while the relationship and mutual influences of the public sector audit and the investment climate are clearly insufficiently investigated. One of the few works investigating public sector auditing activities in the context of the impact on investment is devoted to assessing the impact of auditors' professional and personal characteristics on the quality of the audit when evaluating investment projects (Al‐Fatlawi, 2018).…”
Section: Introductionmentioning
confidence: 99%